Bibliometric analysis of the scientific production on inguinal hernia surgery in the web of science - Carhuallanqui-Ciocca, Eros Ignacio; Echevarría-Quispe, Johssy Yelma; Hernández-Vásquez, Akram; Díaz-Ruiz, Renato; Azañedo, Diego (Frontiers in Surgery, 2023)
Objectives To describe the bibliometric characteristics of the world scientific production in inguinal hernia surgery using the Web of Science Core Collection (WoS) database. Materials and methods A search for original articles published in the WoS up to December 2021 was carried out. Bibliometric analysis was performed using the Bibliometrix data package in R and VOSviewer, version 1.6.17. Results A total of 3,795 articles were identified in the database, with an annual average of 81 published articles and sustained growth with the highest number of publications in 2021. The article “Wide Variation and Excessive Dosage of Opioid Prescriptions for Common General Surgical Procedures” published in 2017 was the most cited (517 citations). The United States was the country of the corresponding author with the highest number of published articles (725 articles). The author with the highest number of published articles was Rosenberg J., affiliated with the University of Copenhagen, with 52 articles and 765 citations. The journal “Hernia” had the highest number of articles published on inguinal hernias in the WoS, representing 18% of the total number of articles. Finally, the keywords most used were “herniorrhaphy” and “hernioplasty” in 2008, and more recently: “single incision” “society guidelines” and “single port”. Conclusions The scientific production of original articles on inguinal hernia surgery has increased. There is currently great interest in research on minimally invasive surgical methods and standardization of procedures based on clinical practice guidelines.